Population Dynamics and Transcriptomic Responses of Chorthippus albonemus (Orthoptera: Acrididae) to Herbivore Grazing Intensity - Qin, Xinghu; Ma, Jingchuan; Huang, Xunbing; Kallenbach, Robert L.; Lock, T. Ryan; Ali, Md. Panna; Zhang, Zehua (Frontiers in Ecology and Evolution, 2017)
Livestock grazing can trigger outbreaks of insect pests in steppe ecosystems of Inner Mongolia in China. However, the physiological responses of the grasshopper Chorthippus albonemus to grazing are not well understood. Here we investigated the effects of sheep grazing on the population dynamics and transcriptomic response of C. albonemus. We collected the insects three times (about 20 days apart) in 1.33-ha plots in which there were no grazing, light grazing, moderate grazing, heavy grazing, or overgrazing. Our results showed that continuous grazing significantly decreased plant biomass and influenced plant succession. Total insect species diversity significantly declined along the grazing intensity gradient and over time. Results of the first two collections of C. albonemus indicated that moderate grazing significantly increased the abundance of C. albonemus. However, abundance was significantly decreased in plots that were overgrazed, possibly because of food stress and environmental pressures. Under moderate grazing, betA and CHDH genes were significantly upregulated in C. albonemus. In response to higher grazing intensity, upregulated genes included those involved in serine-type peptidase activity, anatomical structure development, and sensory organ development; downregulated genes included those involved in the structural constituents of the ribosome and ribosome processes. Genes strongly upregulated in response to heavy grazing pressure included adaptive genes such as those encoding ankyrin repeat domain-containing protein and HSP. These findings improve our understanding of the role of the transcriptome in C. albonemus population response to livestock grazing and may provide useful targets for grasshopper control.